2018
DOI: 10.1139/cjas-2016-0188
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of milk lipid synthesis by exogenous C16:0 and C18 fatty acids in bovine mammary epithelial cells

Abstract: The objective of this study was to examine the effects of removing one fatty acid from a combination of long-chain fatty acids (LCFA) on milk lipogenesis in bovine mammary epithelial cells. The incubation concentration of LCFA was determined, and 100 μmol L−1 of C16:0, 5 μmol L−1 of C18:0, 100 μmol L−1 of cis-9 C18:1, 25 μmol L−1 of n-6 C18:2, and 1.2 μmol L−1 of n-3 C18:3 were used in the study. Treatments were C16:0, C18:0, C18:1, C18:2, and C18:3 combinations as control; control absent of C16:0 as A-C16:0; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…In a study, similar to our study, it was emphasized that the relationships between milk fat and C14:0, C18:0 and C18:1 ω9 fatty acids were at a significant level, and that the C18:3 ω3 level should be evaluated (22). While medium-chain fatty acids are synthesized de novo in the mammary gland, fatty acids longer than C16:0 pass into milk through the circulatory system (23,24). The statistical significance of medium-chain fatty acids in our study suggested that it may be related to the activity in mammary epithelial cells.…”
Section: Discussionsupporting
confidence: 79%
“…In a study, similar to our study, it was emphasized that the relationships between milk fat and C14:0, C18:0 and C18:1 ω9 fatty acids were at a significant level, and that the C18:3 ω3 level should be evaluated (22). While medium-chain fatty acids are synthesized de novo in the mammary gland, fatty acids longer than C16:0 pass into milk through the circulatory system (23,24). The statistical significance of medium-chain fatty acids in our study suggested that it may be related to the activity in mammary epithelial cells.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, fatty acids longer than C16:0 come into the milk from the bloodstream and originate from the ration (55). It has been thought that the main reason for the difference in C16:0 as well as short and medium-chain fatty acids may be related to the activity of mammary epithelial cells in the related breeds (16). Although it has been reported that fatty acids longer than C16:0 are associated with the diet, C17:1, C18:1 and C18:2, C20:0, C22:6 n3 were observed to be different between breeds.…”
Section: Resultsmentioning
confidence: 99%
“…The design of the current study allowed analysis of cytosolic and media FA profiles which has not been reported previously. There are cell culture studies that have examined the effect of FA on transcriptional regulation ( Dan et al., 2018 ) and FA profile of cytosolic TG ( Jacobs et al., 2013 ). Other studies have focused on different aspects of mammary physiology such as enzymatic activity and gene expression ( Peterson et al., 2004 , Yonezawa et al., 2004a , Yonezawa et al., 2004b , Keating et al., 2008 , Sorensen et al., 2008 ).…”
Section: Resultsmentioning
confidence: 99%